2018
DOI: 10.1002/eat.22949
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in healthcare‐detected incidence of anorexia nervosa and bulimia nervosa in the Norwegian National Patient Register (2010–2016)

Abstract: Objective: Few studies have investigated temporal trends in the incidence of eating disorders (EDs). This study investigated time trends in the age-and sex-specific incidence of healthcaredetected anorexia nervosa (AN) and bulimia nervosa (BN) from 2010 to 2016. Methods: Data were retrieved from the Norwegian National Patient Register as defined by the International Classification of Diseases (ICD-10): narrowly defined AN (F50.0), broadly defined AN (F50.0 + 50.1), narrowly defined BN (F50.2), and broadly defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 47 publications
7
45
1
1
Order By: Relevance
“…The age at first‐time diagnosis of BN peaked at 20–29 years in our study, which is older than that in most European countries (Micali et al, ; Smink et al, ; Steinhausen & Jensen, ). Similar to AN, the percentage of the incident BN cases who were older than 30 years in Taiwan was also higher than in Western countries (47% vs. 15–30%) (Micali et al, ; Reas & Ro, ; Steinhausen & Jensen, ). There was a steep increase in the incidence rates of BN in the age groups of 30–39 years and 40–49 years in addition to a small increase in the 20–29 years age group from 2002 to 2007 or 2009.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The age at first‐time diagnosis of BN peaked at 20–29 years in our study, which is older than that in most European countries (Micali et al, ; Smink et al, ; Steinhausen & Jensen, ). Similar to AN, the percentage of the incident BN cases who were older than 30 years in Taiwan was also higher than in Western countries (47% vs. 15–30%) (Micali et al, ; Reas & Ro, ; Steinhausen & Jensen, ). There was a steep increase in the incidence rates of BN in the age groups of 30–39 years and 40–49 years in addition to a small increase in the 20–29 years age group from 2002 to 2007 or 2009.…”
Section: Discussionmentioning
confidence: 98%
“…Whether the incidence of eating disorders (EDs) has changed over time has been a subject of debate (Smink et al, ). Earlier case register studies showed that the incidence of anorexia nervosa (AN) increased before the 1970s (Hoek, ; Keel & Klump, ), whereupon it seemed to stabilize throughout the 2000s (Currin, Schmidt, Treasure, & Jick, ; Smink et al, ; Steinhausen & Jensen, ; Van Son, Van Hoeken, Bartelds, Van Furth, & Hoek, ) and 2010s (Currin et al, ; Keel & Klump, ; Reas & Ro, ; Steinhausen & Jensen, ). Furthermore, studies indicated that after an initial surge in the bulimia nervosa (BN) incidence in the 1980s (Smink et al, ) and 1990s (Currin et al, ), it stabilized (Micali, Hagberg, Petersen, & Treasure, ) or decreased (Currin et al, ; Reas & Ro, ; Smink et al, ) during the 2000s and 2010s.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations